The Effect of Digital Leadership Style on Employee Work Motivation with Role Ambiguity as A Mediating Variable - Liony Gita; Chandra Wibowo Widhianto (Enrichment: Journal of Multidisciplinary Research and Development, 2026)
This research aims to analyse the influence of digital leadership on work motivation and examine the role of role ambiguity as a mediating variable. This study used a quantitative approach using Partial Least Squares–Structural Equation Modelling (PLS-SEM) method. Data were obtained through questionnaires distributed to respondents working in organisations implementing digital transformation. The results of the study indicate that digital leadership has a positive and significant effect on work motivation. Furthermore, digital leadership also significantly reduces role ambiguity. However, role ambiguity was not shown to significantly influence work motivation and did not act as a mediator in the relationship between digital leadership and work motivation. These findings confirm that digital leadership plays a direct role in enhancing employee work motivation, particularly in the context of organisations adapting to technological change. This research provides theoretical contributions to the development of digital leadership literature and offers practical implications for organisations in strengthening leadership effectiveness in the era of digital transformation.